Immigrant fertility in Germany: The role of culture - Kamila Cygan-Rehm (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper focuses on the role of home country's fertility culture in shaping immigrants' fertility. I use the German Socio-Economic Panel (SOEP) to study completed fertility of first-generation immigrants who arrived from different countries and in different years. The variation in total fertility rates (TFRs) across countries and over time serves as a proxy for cultural changes. By using a linear fixed-effects approach, I find that women from countries with high TFRs have significantly more children than women from countries with low TFRs. I also demonstrate that this positive relationship is attenuated by potential selection that operates towards the destination country. In addition, home country's TFRs explain a large proportion of fertility differentials between immigrants and German natives. The results suggest that home country's culture affects immigrants' long-run outcomes, thereby supporting the socialization hypothesis. – – Diese Studie befasst sich mit dem Geburtenverhalten von Migrantinnen der ersten Generation. Unter Verwendung der Daten des Sozio-oekonomischen Panels (SOEP) wird die endgültige Kinderzahl der Zuwanderinnen als abhängige Variable und die kulturelle Prägung aus dem Heimatland als Determinante modelliert. Zur Messung der "Fertilitätskultur" wird als Proxy die mittlere Differenz zwischen der zusammengefassten Geburtenziffer (total fertility rate - TFR) des Ursprungslandes und der von Deutschland zum Zeitpunkt der Migration verwendet. Die Schätzergebnisse eines linearen Fixed-Effects-Ansatzes zeigen, dass Fertilitätskultur einen signifikanten Anteil der Fertilitätsunterschiede zwischen Einheimischen und Migranten erklärt und positiv mit der endgültigen Kinderzahl der Migrantinnen korreliert. Ergänzende Analysen legen nahe, dass der positive Zusammenhang durch potenzielle Selektion tendenziell unterschätzt wird. Die Befunde unterstreichen die sogenannte Sozialisationshypothese, welche besagt, dass die kulturelle Prägung des Ursprungslandes das Verhalten von Migranten dauerhaft beeinflusst.
Keywords: J13; J15; Z10; Z13; 330; migration; fertility; socialization; culture; Germany